2011
DOI: 10.4187/respcare.00938
|View full text |Cite
|
Sign up to set email alerts
|

Chair-Sitting Exercise Intervention Does Not Improve Respiratory Muscle Function in Mechanically Ventilated Intensive Care Unit Patients

Abstract: BACKGROUND: Chair-sitting may allow for more readily activated scalene, sternocleidomastoid, and parasternal intercostal muscles, and may raise and enlarge the upper thoracic cage, thereby allowing the thoracic cage to be more easily compressed. OBJECTIVE: To evaluate the effect of chair-sitting during exercise training on respiratory muscle function in mechanically ventilated patients. METHODS: We randomized 16 patients to a control group and 18 patients to a chairsitting group. The patients in the chair-sitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…PCT did not elicit any significant changes in respiratory parameters in comparison to resting supine, results that concur with those found in a recent similar study [ 14 ]. This study also reported a significant increase in HR beyond activity completion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PCT did not elicit any significant changes in respiratory parameters in comparison to resting supine, results that concur with those found in a recent similar study [ 14 ]. This study also reported a significant increase in HR beyond activity completion.…”
Section: Discussionsupporting
confidence: 92%
“…Emerging evidence for early mobilisation demonstrates reduction in the number of ventilator days and hospital length of stay [ 7 , 8 ], as well as improving functional outcomes at hospital discharge [ 9 11 ]. Early mobilisation within this patient cohort involves a combination of passive exercise including positioning, joint range of movement, and hoist transfer to chair; and more active tasks including sitting on the edge of the bed (SOEOB), step transfer to a chair and ambulation [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches included flow resistive training (one study) (55), diaphragmatic breathing exercises (two studies) (48,53), and biofeedback on respiratory pattern (one study) (39). More general physical therapy regimens were also studied for their effect on inspiratory muscle strength, including mobilization (48,56,58), postural training (36,42), and upper arm exercise (44). Some studies employed combinations of these techniques.…”
Section: Original Researchmentioning
confidence: 99%
“…IMT was applied after 24 hours of mechanical ventilation (1 study) (35), once patients were awake and cooperative (1 study) (48), once the patient was transitioned to partially assisted ventilation (1 study) (34), once patients met readiness-to-wean criteria (5 studies) (37,38,41,49,50), once patients failed attempted weaning (12 studies) (39, 40, 45-47, 52-55, 57, 59, 60), or after liberation from ventilation (3 studies) (33,43,44). Four studies did not specify the timing of intervention (36,51,56,58). The duration of IMT varied widely between studies, ranging from 3 days to up to 6 weeks of therapy (Table 1).…”
Section: Original Researchmentioning
confidence: 99%
“…Despite long-standing evidence that prolonged bed rest results in deconditioning [ 1 , 2 ], studies investigating the effectiveness of early progressive mobilization for ICU patients have only started appearing in the literature in the last 10 to 15 years [ 3 , 4 ]. While the earlier publications documented the feasibility, safety and physiological effects associated with the mobilization of ICU patients [ 5 - 8 ], point-prevalence studies [ 9 , 10 ] and controlled trials investigating the effectiveness of early progressive mobilization have been published in more recent years [ 11 - 16 ]. These studies, and concomitant systematic reviews [ 4 , 17 - 22 ], provide evidence that early progressive mobilization of adult ICU patients is feasible, safe, and may result in benefits including improved functional outcomes, and reduced ICU and hospital length of stay.…”
Section: Introductionmentioning
confidence: 99%